2015
DOI: 10.1371/journal.pone.0140385
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Corvis ST Tonometry Measured Corneal Parameters and Intraocular Pressure, Corneal Thickness and Corneal Curvature

Abstract: The purpose of the study was to investigate the correlation between Corneal Visualization Scheimpflug Technology (Corvis ST tonometry: CST) parameters and various other ocular parameters, including intraocular pressure (IOP) with Goldmann applanation tonometry. IOP with Goldmann applanation tonometry (IOP-G), central corneal thickness (CCT), axial length (AL), corneal curvature, and CST parameters were measured in 94 eyes of 94 normal subjects. The relationship between ten CST parameters against age, gender, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 47 publications
10
45
4
Order By: Relevance
“…The current study also confirmed the significant negative associations among axial length and A2T, A2V, and radius, reported by Asaoka et al 35 Lee et al 36 reported significantly larger A2V and PD values in myopic subjects, which agrees with those from the current study. 36 Together, the current study confirmed more comprehensively the results of the previous investigations that myopic eyes have less corneal deformation.…”
Section: Axial Lengthsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study also confirmed the significant negative associations among axial length and A2T, A2V, and radius, reported by Asaoka et al 35 Lee et al 36 reported significantly larger A2V and PD values in myopic subjects, which agrees with those from the current study. 36 Together, the current study confirmed more comprehensively the results of the previous investigations that myopic eyes have less corneal deformation.…”
Section: Axial Lengthsupporting
confidence: 93%
“…The significant association between age and A2T reported in another previous study 35 was confirmed by the current study, but the current study did not confirm the associations of age with other parameters (A1T, A2V, radius, and HCDA) reported in the same paper. The inconsistencies among studies might be due to differences in statistical analyses and study populations.…”
Section: Agecontrasting
confidence: 72%
See 1 more Smart Citation
“…To determine the independent factors of the pNFE, the optimal linear models were selected among all possible combinations of the predictors based on the second order bias corrected Akaike Information Criterion index. 26,27 …”
Section: Statistical Analysesmentioning
confidence: 99%
“…4 Moreover, biomechanical measurements of the cornea are confounded by other parameters, such as IOP 5,6 and central corneal thickness (CCT). 5,7 Thus, providing an accurate measurement of corneal mechanical parameters (e.g., Young's modulus) is not straightforward, let alone based on applanation measurements. Nevertheless, commercially available noncontact tonometers (e.g., the ocular response analyzer and CorVis ST) can distinguish between healthy and keratoconic corneas, 8 but there have been conflicting results on their ability to detect corneal biomechanical changes due to therapeutic interventions such as corneal collagen crosslinking.…”
mentioning
confidence: 99%